Bilateral Rostral Mandibulectomy for the Management of Oral Tumor in Dogs: A Report of Two Cases - Reddy, Puli Vishnu Vardhan; Shafiuzama, Mohammed; Simon, Shiju; Raj, Pushkin; Ratnam, Thenmozhi; Sagare, Rajat (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
eoplasia in the oral cavity is the fourth most common  site, accounting for about 5% of all malignant tumors  detected in dogs and 7% in cats (Fossum et al., 2002). Bilateral  rostral mandibulectomy involves the excision of a portion of  the rostral aspect of both mandibles (Lantz 2012). The primary  reason for performing a bilateral rostral mandibulectomy in  dogs is to surgically remove benign or malignant oral tumors  that extend across the midline rostral to the mandibular first  premolar teeth (Smithson and Taney 2009). Although bilateral  rostral mandibulectomy leads to mandibular prognathism,  the cosmetic result and prehension and mastication functions  are generally excellent (Salisbury 2003). This document  presents a successful bilateral rostral mandibulectomy in  two dogs with oral tumors without mandibular fixation and  with cosmetic reconstruction of the lower lip without tension.
Keywords: Bilateral Rostral; cosmetic